Do soda taxes affect the consumption and health of school-aged children? Evidence from France and Hungary - Selina Gangl (ZBW - Leibniz Information Centre for Economics, 2021)
This paper examines the effect of two different soda taxes on consumption behaviour and health of school-aged children in Europe: Hungary imposed a Public Health Product Tax (PHPT) on several unhealthy products in 2011. France introduced solely a soda tax, containing sugar or artificial sweeteners, in 2012. In order to exploit spatial variation, I use a semi-parametric Difference-in-Differences (DID) approach. Since the policies differ in Hungary and France, I analyse the effects separately by using a neighbouring country without a soda tax as a control group. The results suggest a counter-intuitive positive effect of the tax on soda consumption in Hungary. The reason for this finding could be the substitution of other unhealthy beverages, which are taxed at a higher rate, by sodas. The effect of the soda tax in France is as expected negative, but insignificant which might be caused by a low tax rate. The body mass index (BMI) is not affected by the tax in any country. Consequently, policy makers should think carefully about the design and the tax rate before implementing a soda tax.
Keywords: H25; I12; I18; L66; 330; Soda tax; consumption; health; semi-parametric difference-in-differences; HBSC